Pengaruh Manajemen Kelas Virtual Terhadap Motivasi Belajar Daring Peserta Didik - Romadhon, Maulida; Muhayat, Imam; Qosim, Achmad (Tahta Media Group, 2022)
Classroom management is a conscious effort to systematically organize teaching and learning process activities that lead to success, which has a relationship with the encouragement of students to actively learn even though the implementation of the teaching and learning process is online. The purpose of this study was to determine whether there is a significant relationship between virtual classroom management and students' online learning motivation and how much virtual classroom management contributes to students' online learning motivation at Madrasah Ibtidaiyah Kalifa Nusantara for the 2020/2021 academic year. This type of quantitative research uses systematic scientific research on the parts and phenomena and the causality of their relationships. The results showed that: 1) There was a significant relationship between virtual classroom management and online learning motivation of students at Madrasah Ibtidaiyah Kalifa Nusantara. This is indicated by the virtual classroom management variable, which has a positive regression coefficient towards online learning motivation of 38.355, meaning that if virtual classroom management has an increase of 1 point, online learning motivation will increase by 38.355. It is also known that the count of 6.360 is more excellent than the table at a significant level of 5%, which is 1.693. This means that Ho is rejected and Ha is accepted, so it is stated that the correlation of the X variable with the Y variable is significant. 2) The virtual class management variable (X) has a simultaneous contribution of 57.4 to the online learning motivation variable (Y), and the remaining 42.6% is influenced by other factors not examined by the author.